Redescription of the genus Wachsiella (Hemiptera: Heteroptera: Largidae: Physopeltinae) with description of male and comments on its tribal placement - Stehlík, Jaroslav L.; Hemala, Vladimír; Kment, Petr (Zootaxa, 2016)
A detailed redescription (including first description of the male sex) of the genus Wachsiella Schmidt, 1931 (Hemiptera: Heteroptera: Largidae: Physopeltinae) and its single species, Wachsiella horsti Schmidt, 1931, is provided. The systematic placement of the genus is discussed and it is placed in the tribe Physopeltini. Wachsiella horsti is a species endemic to south Sulawesi (Indonesia), known only from specimens collected in 1895–1896 and has never been reported since.